PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PT ADIRA DINAMIKA MULTI FINANCE TBK DAN PT ASTRA SEDAYA FINANCE - Andriani, Ifa; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of liquidity and profitability on firm value at PT Adira Dinamika Multi Finance Tbk and PT Astra Sedaya Finance. The research method used is an associative method with a quantitative approach. The data used are secondary data in the form of financial statements for the period 2019–2023. Liquidity is measured using the Current Ratio (CR), profitability is measured using Return on Assets (ROA), and firm value is measured using Price to Book Value (PBV). The data analysis techniques used include multiple linear regression analysis, classical assumption tests, and hypothesis testing consisting of partial tests (t-test) and simultaneous tests (F-test). The results show that liquidity has no significant effect on firm value, while profitability has a positive and significant effect on firm value. Simultaneously, liquidity and profitability have a significant effect on firm value.